2019
DOI: 10.3389/fendo.2019.00607
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Level Impairs Human Mature Bone Marrow Adipocyte Function Through Increased ROS Production

Abstract: Bone marrow adipocytes (BMAds) accumulate in aging, menopause, and metabolic diseases such as Type 2 diabetes. These osteoporotic conditions are associated with oxidative stress and hyperglycemia which are both considered as critical factors underlying bone fragility. Glucose excess and reactive oxygen species (ROS) are known to favor adipogenesis over osteoblastogenesis. In this study, we investigated whether high glucose exposure could determine dysfunction of mature BMAds, specifically through ROS productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 76 publications
3
13
0
Order By: Relevance
“…This high glucose-induced biological reaction is associated with ROS-mediated Akt attenuation (Cheng et al, 2016). Consistent with previous studies, Rharass et al showed that intracellular and extracellular ROS concentrations were significantly increased by 50% under high glucose exposure, paralleled by increased mRNA levels of the H 2 O 2 generating enzyme NADPH oxidase 4 (Rharass and Lucas, 2019). All of the studies reviewed here support the notion that hyperglycemia drive mitochondrial dysfunction through the ROS pathway which is fundamental to the senescence of MSCs.…”
Section: Mitochondrial Dysfunction and Oxidative Stresssupporting
confidence: 91%
See 1 more Smart Citation
“…This high glucose-induced biological reaction is associated with ROS-mediated Akt attenuation (Cheng et al, 2016). Consistent with previous studies, Rharass et al showed that intracellular and extracellular ROS concentrations were significantly increased by 50% under high glucose exposure, paralleled by increased mRNA levels of the H 2 O 2 generating enzyme NADPH oxidase 4 (Rharass and Lucas, 2019). All of the studies reviewed here support the notion that hyperglycemia drive mitochondrial dysfunction through the ROS pathway which is fundamental to the senescence of MSCs.…”
Section: Mitochondrial Dysfunction and Oxidative Stresssupporting
confidence: 91%
“…However, GDM-UCMSCs demonstrated a significantly lower adipogenic potential (Kim et al, 2015;Moseley et al, 2018). Furthermore, another study found that BMSCs showed decreased adipogenic differentiation capability under high glucose conditions and that the mRNA expression of peroxisome proliferator activated receptor gamma, CCAAT/enhancerbinding protein alpha, leptin, and adiponectin in BMSCs decreased (Rharass and Lucas, 2019). Interestingly, when cultured in an appropriate induction medium, both AMSCs from diabetic donors (dAMSCs) and from non-diabetic donors (nAMSCs) exhibited potential for trans-differentiation into neuron-like cells via a reactive oxygen species (ROS)-mediated mechanism (Cheng et al, 2016).…”
Section: Differentiationmentioning
confidence: 99%
“…Under normal physiological conditions, the surrounding tissues respond to insulin by increasing the expression of glucose transporters on the plasma membrane. However, consistent high glucose levels and consequent long-term high insulin levels will lead to insulin resistance [ 134 ]. High levels of insulin interfere with NOX4 signal transduction and enhance ROS production [ 135 ].…”
Section: High Glucosementioning
confidence: 99%
“…To simulate an uncontrolled diabetic state, we designed to culture the cells in 25-mM glucose and investigated the effect of high glucose on the viability of RSC96 cells. The 5.6-mM glucose medium is close to physiological levels [ 34 , 35 , 36 , 37 ]. Cell viability was measured by CCK 8 (cell counting kit 8) assay.…”
Section: Resultsmentioning
confidence: 99%